Design Criteria of Vertical Housing for Social Communities - Maharani, Rizka Tiara; Harmunisa, Yusvika Ratri; Almahmudah, Almahmudah; Oktavianti, Cindy (RUAS, 2023)
Population growth, increased housing requirements, and a lack of available land in urban areas motivate developers to construct vertical housing. Vertical occupancy reduces social interaction between occupants, leading to the development of individualistic characteristics. This is due to the fact that the design does not encourage inhabitants to interact with one another. This research seeks to identify the design criteria necessary to construct a social structure in a vertical residence. This study's methodology consisted of three stages: data collection, analysis, and synthesis. Where quantitative and qualitative data are collected using a combined research methodology. Retrieve quantitative data through questionnaires to ascertain the social interaction habits of vertical occupancy users. While qualitative methods, such as literature and precedent studies, such as Home Farm Singapore and The Rosebay Surabaya, are used to identify existing issues. The analysis phase consists of descriptive statistics to interpret the questionnaire results, as well as a description of the analysis based on the research variables used, such as accessibility, users, individuality, adaptability, and others. The results of the synthesis phase will be design criteria that can enhance the social value of vertical housing